Science & Technology in Select Foursouth Asia Countries: A Scientometric Analysis of Publications, 1996-2011 - Gupta, Ritu; Gupta, B. M. (Journal of Information and Knowledge, 2014)
The comparative research output in S&T of four South Asia countries, namely Pakistan, Bangladesh, Sri Lanka and Nepal has been analyzed during 2001-11. It focused on their publication growth, publication share in global output, share of international collaborative publications and broad and narrow subject areas of focus. The data covered in this study has been derived from SClmago Journal and Country Rank website (http://www.scimagojr.com), which is based on Scopus database.